2023
DOI: 10.3390/foods12061177
|View full text |Cite
|
Sign up to set email alerts
|

Mexican Ancestral Foods (Theobroma cacao, Opuntia ficus indica, Persea americana and Phaseolus vulgaris) Supplementation on Anthropometric, Lipid and Glycemic Control Variables in Obese Patients: A Systematic Review and Meta-Analysis

Abstract: Diet containing Mexican ancestral foods such as cocoa, nopal, avocado, and common bean have been individually reported to have beneficial effects on obesity and comorbidities. Methods: A systematic review and meta-analysis on the effect of Mexican ancestral foods on the anthropometric, lipid, and glycemic control variables in obese patients was performed following PRISMA guidelines. Data were analyzed using a random-effects model. Results: We selected 4664 articles from an initial search, of which only fifteen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…High CHOL, LDL, and TG concentrations are frequently associated with atherosclerotic plaque formation and atherosclerosis, contributing to increased cardiovascular events 31,32 . Our results corroborate those of Ganesan et al (2017), who showed that P. vulgaris contains phytosterols that could reduce LDL cholesterol 33 . The ions Na + , K + , Cl -, and Ca 2+ ensure in the organism the transmission of the nervous impulse, the frequency of cardiac beats, the levels of systole and diastole in the heart, and the vascular tonus.…”
Section: Evolution Of Biochemical and Hematologicalsupporting
confidence: 93%
“…High CHOL, LDL, and TG concentrations are frequently associated with atherosclerotic plaque formation and atherosclerosis, contributing to increased cardiovascular events 31,32 . Our results corroborate those of Ganesan et al (2017), who showed that P. vulgaris contains phytosterols that could reduce LDL cholesterol 33 . The ions Na + , K + , Cl -, and Ca 2+ ensure in the organism the transmission of the nervous impulse, the frequency of cardiac beats, the levels of systole and diastole in the heart, and the vascular tonus.…”
Section: Evolution Of Biochemical and Hematologicalsupporting
confidence: 93%
“…In addition, the extraction yield and structural properties of kidney bean NSPs differ among cultivars, which may guide the development of plant-based novel functional components. However, review articles on kidney beans in recent years mainly focused on the following aspects: (1) nutritional and functional properties of kidney beans together with other legumes from the regions of India, 29 Mexico, 30 Europe, 31 and Africa; 32 (2) food processing technologies; 33–36 (3) potential strategies to improve metabolic health with a white kidney bean extract, 10 prevent cardiovascular diseases with kidney bean bioactive compounds, 37 inhibit noncommunicable chronic diseases, 38 and alleviate diabetes and obesity with kidney bean α-amylase inhibitors. 39 To the best of our knowledge, there is no report, to date, comprehensively reviewing kidney bean NSPs, including their extraction, structural characterization, biological function, and interaction with other nutrients.…”
Section: Introductionmentioning
confidence: 99%